World Internet Development Report 2019 Blue Book for World Internet Conference, Translated by CCTB Translation Service. - Chinese Academy of Cyberspace Studies; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This book systematically reviews world Internet development over the past 50 years, and comprehensively discusses the great contributions it has made to economic and social advances. Further, it describes the development, status and trends related to the Internet in major countries around the globe in 2019, and provides an in-depth analysis of the latest conditions, dynamics and development trends in key areas, including information infrastructure, information technology, digital economy, digital government, Internet media, cyberspace security, and international cyberspace governance. Moreover, the book further modifies and enhances the Global Internet Development Index System, in order to better show the Internet development strengths and advantages in various countries, and to reflect the global development trends more comprehensively, accurately and objectively. This book reviews the significant developments and summarizes the lessons learned as well as the future challenges. From a global perspective, it offers a vision of building a community with a shared future in cyberspace based on the new concepts, new ideas and new achievements of various countries participating in cyberspace development and construction. As such it is a valuable reference resource for anyone working in Internet related fields, such as those in government departments, internet enterprises, scientific research institutions, colleges and universities wanting to fully understand world Internet development.
World Internet Development in 50 Years -- General Introduction -- Development of World Information Infrastructure -- Development of World Network Information Technology -- Development of World Digital Economy -- Development of World Digital Government -- Development of World Internet Media -- Development of World Network Security -- International Cyberspace Governance -- Afterword.
Keywords: Telecommunication; Application software; Electronic commerce; Signal processing; Industrial Management; Technology; History; Communications Engineering, Networks; Computer and Information Systems Applications; e-Commerce and e-Business.; Signal, Speech and Image Processing .; Industrial Management; History of Technology